Comparison between prognostic indicators in organ insufficiency with acute pancreatitis - Duzenci, Deccane; Yalniz, Mehmet; Ispiroglu, Murat (Turkish Assoc Trauma Emergency Surgery, 2021)
BACKGROUND: Organ failures that develop due to acute pancreatitis (AP), some laboratory values and the anthropometric characteristics of the patients have been shown to play a role in the prognosis AP and have been increasingly used to investigate the prognosis of the disease although classification systems, such as Ranson's criteria, are still used habitually. In this stud, we aimed to investigate the relationship of the organ failures observed during the course of AP, the biochemical parameters and the anthropometric characteristics of the patients and compare using Ranson's and Atlanta Classifica-tion (AC) systems. METHODS: Laboratory values, anthropometric data, including the waist circumference and body mass index, Systemic inflammatory response syndrome (SIRS) and organ failures developed during the course of the disease, were investigated prospectively in 153 AP patients and the Ranson and Modified Atlanta Classifications (MAC) were made. RESULTS: A relationship was observed between the organ failures that were established in the course of the disease (lung, liver, kidney, heart and MOF (multiple organ failure)) and higher Ranson's and MAC scores (p<0.05). Among the patients included in this study, 13 (8.4%) had multiple organ failure and 17 (11.1%) had SIRS. Exitus occurred in 10 patients (6.5%). A statistically significant relationship was found with organ failure, multiple organ failure and SIRS; and ensuing exitus (p<0.05). While no relationship was observed between the waist circumference, body mass index, Ranson's score, there was a significant relationship between the MAC and the waist circumference (p<0.01). Among the laboratory values, high urea and ALT values showed a relationship with the Ranson and MAC (p<0.001), while between the CRP values tested at the 0 time point and the 48th hour, only the CRP value at the 48th hour had a relationship with Ranson's score (p<0.05). Organ failure, MOF, and SIRS showed a correlation with both the severity scores and the mortality rate. In addition, a significant corre-lation was observed between the cholesterol, triglycerides and the CRP level at the time of hospitalisa-tion and mortality. On the contrary, no significant relationship was observed with the other laboratory results, including calcium, lipase and hematocrit. CONCLUSION: In conclusion, to determine the severity and prognosis of acute pancreatitis, and ex-pect the organ failures that may occur in severe pancreatitis, the body mass index, waist circumference and laboratory values, including cholesterol, triglycerides, ALT, and CRP may supply important prog-nostic data besides the conventional disease severity scoring methods.
Akut pankreatitde organ yetersizliğinin önemi ve prognostik belirteç sistemleri ile karşılaştırılması
Keywords: Acute pancreatitis; organ failure; severity scoring